Inhibitory tagging in inhibition of return: evidence from flanker interference with multiple distractor features. - Vivas, AB; Fuentes, L; Estevez, A; Humphreys, G (2007)
Fuentes, Vivas, and Humphreys (1999) proposed a distinction between inhibition of return (IOR) and inhibitory processing taking place at a location subject to IOR. This latter mechanism, inhibitory tagging (IT), would act at a late level of processing related to response selection. In the present study, we examined whether IT was applied only to the target-relevant properties of the stimuli (e.g., to its color) or whether it was applied to other features of the stimulus as well (e.g., to its shape). Both when the task was to respond to the target's color (Experiment 1) as well as when it was to respond to the target's shape (Experiment 2), there was evidence of IT (reversal of the typical flanker effect at the cued location, relative to the uncued location) only to task-relevant features of the target. These findings suggest that IT is a central process of control constrained by task demands and current goals.